Selective mono- and dimetallation of a group 3 sandwich complex. Issue 65 (26th July 2019) - Martínez-Martínez, Antonio J.; Kennedy, Alan R.; Paprocki, Valerie; Fantuzzi, Felipe; Dewhurst, Rian D.; O'Hara, Charles T.; Braunschweig, Holger; Mulvey, Robert E.
Abstract : While lithium alkyls and lithium amides do not metallate the scandium compound [(η 5 -C5 H5 )Sc(η 8 -C8 H8 )], a synergistic lithium–aluminium base-trap partnership cannot resist taking a bite with one C–H bond selectively cleaved from both Cp and COT rings. Abstract : The scandium Cp/COT hybrid sandwich compound [(η 5 -C5 H5 )Sc(η 8 -C8 H8 )] is resistant to metallation via conventional alkyllithium and lithium amide bases. In this work, clean, selective, stoichiometric and high-yielding mono- and dimetallation is accomplished using tandem trans -metal-trapping (TMT) involving LiTMP and iBu2 AlTMP with deprotonation occurring selectively at the Cp and Cp/COT rings respectively, providing the first examples of selective metallation of a sandwich complex featuring a group 3 element.